High-manganese phosphate positive electrode material and application thereof in sodium ion battery
By accurately controlling the doping of transition metal ions in the positive electrode material of sodium ion battery and building a carbon cladding layer, the structural distortion problem of the material during the charging and discharging process is solved, the rate performance and cyclic stability are significantly improved, and high capacity and good electrochemical performance are achieved.
Patent Information
- Application Number
- CN202311268178.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The existing sodium ion battery positive electrode materials have Ginger Taylor distortion during charging and discharging, resulting in problems such as collapse of sodium ion diffusion channel, dissolution of transition metals, and mixed discharge of alkali metal ions and transition metal ions, resulting in a decrease in rate performance and a worse cycle stability.
By accurately controlling the co-doping of manganese ions, vanadium ions and other transition metal ions, the redox potential of the positive electrode unit cell structure is enhanced, and the carbon coating is constructed through different carbon sources and reducing agents is suppressed to inhibit the dissolution behavior of manganese ions during the cycle and improve the sodium ion transfer rate.
It significantly improves the rate performance and cyclic stability of the material, improves the redox potential and ionic conductance, realizes the reversible electrochemical deintercalation process of inert sodium ions in the structure, and enhances the gram capacity of the material.
Smart Images

Figure CN119725414A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sodium ion batteries and relates to sodium ion battery electrode materials, in particular to phosphate pyrophosphate composite polyanion compound electrode materials, preparation methods and applications of the same in sodium ion battery electrode materials. Background Art
[0002] Vigorously developing clean and renewable energy has become an important development strategy for countries around the world. In order to achieve the continuous and stable integration of renewable energy into the power grid system, supporting energy storage technologies must be developed. Lithium-ion batteries are widely used in large-scale energy storage due to their high energy density and long cycle life. However, in recent years, the problem of lithium source limitation has led to high prices for positive electrode materials for lithium-ion batteries. Sodium is more abundant in the earth's crust and more evenly distributed, so it has a lower price, and sodium ions and lithium ions have similar physical and chemical properties and storage mechanisms. Therefore, sodium-ion batteries show great application potential in user-side energy storage and large-scale energy storage. The positive electrode material is one of the key components that determine the performance of sodium-ion batteries. Therefore, designing a positive electrode material with high specific capacity and high stability is the key to achieving a breakthrough in the practicality of sodium-ion batteries in large-scale energy storage.
[0003] Polyanion-type sodium ion battery positive electrode materials, such as sodium iron (manganese vanadium) phosphate pyrophosphate, have become the preferred positive electrode materials for sodium ion batteries due to their stable structure, high safety, and high redox potential. In this structure, the redox potential of manganese ions and vanadium ions is relatively high, which can increase the overall charge and discharge voltage of the material, thereby increasing the energy density of the sodium ion battery. However, manganese ions and vanadium ions undergo a process of Jan-Taylor distortion during the charge and discharge process, which triggers a series of adverse changes in the unit cell structure, such as collapse of sodium ion diffusion channels, dissolution of transition metals, and mixing of alkali metal ions and transition metal ions, resulting in problems such as decreased rate performance and poor cycle stability. Summary of the invention
[0004] In view of the defects of existing sodium ion battery positive electrode materials, the present invention provides a new structure of phosphate pyrophosphate composite polyanion compound, which precisely regulates the positive electrode unit cell structure by co-doping manganese ions, vanadium ions and other transition metal ions, improves the redox potential of the material, and improves the ionic conductivity and electronic conductivity. By using different types of carbon sources and reducing agents to construct a good carbon coating layer interface, the dissolution behavior of manganese ions in the cycle process is suppressed, and the sodium ion transmission rate is improved. Thereby, the rate performance and cycle stability of the material are improved as a whole.
[0005] Beneficial Effects
[0006] In order to solve the problems of low redox potential and low gram capacity of sodium iron pyrophosphate material itself, the present invention provides a new structure of sodium iron pyrophosphate composite polyanion compound, which improves the redox potential of the structure by precisely controlling the composite ratio of iron, manganese and vanadium, thereby improving the charging and discharging medium voltage of the material.
[0007] At the same time, by constructing partial metal ion doping at transition metal sites (iron, manganese, and vanadium) in the unit cell structure, the ionic conductivity and electronic conductivity of the material are improved, the unit cell structure is stabilized, the band gap of the material is reduced, the reversible electrochemical extraction / embedding process of inert sodium ions in the structure is realized, and the multi-electron transfer process of more than three electrons is realized, thereby increasing the gram capacity of the material.
[0008] At the same time, different carbon sources and reducing agents are selected to achieve uniform carbon coating of the material. Macromolecular carbon is formed through the esterification process of citric acid and ethylene glycol to construct a continuous carbon network, which improves the interfacial conductivity of the material and the reversibility of the sodium ion deintercalation / embedding process. To a certain extent, the volume expansion problem caused by the deintercalation / embedding of sodium ions is alleviated, the lattice stress of the buffer material is used to damage the electrode material, and the dissolution of transition metal ions during the cycle process is inhibited, thereby further improving the cycle stability of the material.
[0009] The present invention improves the ionic conductivity and electronic conductivity of the material by regulating the unit cell structure and using a carbon coating strategy to prepare a phosphate pyrophosphate composite polyanionic compound electrode material, which has high gram capacity, good rate performance and cycle stability as a positive electrode material for a sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 Perform XRD pattern for sample 1#;
[0011] Figure 2 SEM characterization image of sample 1#;
[0012] Figure 3 This is a diagram of the button-type half-cell charge and discharge cycle test for sample 1#. DETAILED DESCRIPTION
[0013] Example 1 - Na4Fe 0.65 Mn 1.75 V 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C
[0014] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10O8, 0.3 mol ethylene glycol C2H6O2, 0.065 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.175 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.03 mol ammonium metavanadate NH4VO3, 0.005 mol chromium nitrate nonahydrate CrN3O9·9H2O, 0.005 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0015] 2) Add 0.4 mol of sodium dihydrogen phosphate dihydrate NaH2PO4.2H2O (sodium source / phosphorus source) to the above aqueous solution, and continue stirring until the raw materials are completely dissolved to obtain a precursor solution;
[0016] 3) Pumping the precursor solution into a spray drying device protected by a nitrogen atmosphere for spray drying (inlet temperature of 160° C., outlet temperature of 95° C., feed flow rate of 60 ml / min, compressed nitrogen pressure of 0.8 KPa) to obtain a precursor powder;
[0017] 4) The precursor powder was then transferred into a high-temperature tube furnace protected by an argon atmosphere for heat treatment. The first stage heat treatment temperature was 400°C and the heat treatment time was 5 h. The second stage heat treatment temperature was 650°C and the heat treatment time was 10 h. The final product was obtained after heat treatment and was recorded as sample 1#.
[0018] 5) Test sample 1# as follows:
[0019] a. Refined-XRD and ICP (main detection elements: Na / Fe / Mn / V / Cr / Al / P) tests. Refined-XRD shows that the product after heat treatment is consistent with the crystal structure of Na4Fe3(PO4)2P2O7, belonging to the R3c space group. Cr and Al are distributed in the transition metal (Fe / Mn) position. ICP test shows that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 4:0.65:1.75:0.3:0.05:0.05:4, which is Na4Fe 0.65 Mn 1.75 V 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0020] b. XPS test was performed on iron, manganese, vanadium, chromium and aluminum elements in sample 1#. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe 2+ , Mn 2+ 、V 3+ Cr 3+ 、Al 3+ ;
[0021] c. The band gap width of the prepared sample 1# was tested by UV-visible absorption spectroscopy, and the test result was 3.25 eV;
[0022] d. XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test were performed on the prepared sample 1#. Figure 1 ) It can be seen that the synthesized material is pure phase (purity up to 99.95%). From SEM ( Figure 2 ) It can be seen that the particle size is uniform and small, with a particle size of 3μm-5μm. From the 1C charge and discharge cycle test of the button half-cell ( Figure 3 ) It can be seen that the positive electrode material has good cycle stability.
[0023] 6) Sample 1# was used as the active material, mixed evenly with the conductive agent acetylene black and the binder polyvinylidene fluoride in a mass ratio of 8:1:1, and an appropriate amount of solvent N-methylpyrrolidone was added to form a paste, which was applied on the aluminum current collector and cut into discs with a diameter of 14 mm after drying. The surface density of the active material was 1.1-3.2 mg / cm 2 (Here is 2.1 mg / cm 2 ), using this as the positive electrode of the battery, the negative electrode is sodium metal, the electrolyte is 1M NaClO4 / EC / DEC / 5%FEC (EC / DEC V / V=1:1), the separator is a glass fiber membrane, and the assembled battery is subjected to charge and discharge tests. The charge and discharge cycles are performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V, and the data of the discharge specific capacity and the discharge medium voltage of the stable cycle are recorded in Table 1. After charging to 4.5V, the positive electrode sheet is disassembled from the battery in the glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0024] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 0.4:0.65:1.75:0.3:0.05:0.05:4, that is, when charged to 4.5V, there are 3.6 reversible sodium ions in the structure for deintercalation;
[0025] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in the above-mentioned pole piece at the same time. The peak separation results showed that the iron and manganese in the above-mentioned pole piece were Fe 3+ , Mn 3+ 、V 5+ Cr 3+ 、Al 3+ , namely Fe 2+ / 3+ and Mn 2+ / 3+A single electron transfer redox reaction occurs between them, and V 3+ / 5+ A two-electron transfer reaction occurs, and Cr 3+ 、Al 3+ No redox reaction occurs in the above process, that is, the number of electron transfers in the above process is > 1e - / valence-changing transition metal ions, the number of sodium ions undergoing redox deintercalation is > 3;
[0026] c. The Re-fined-XRD technique was used to analyze that the volume change of the unit cell during the charge and discharge process was about 2%. During the charge and discharge process, the inert sodium at the Na2 site participated in the redox insertion and extraction, which realized the activation of the inert sodium ions in the unit cell structure.
[0027] 7) At the same time, the capacity retention rate of the battery after the above 1C / 1C cycle 200 times is 90%, which is recorded in Table 1. The battery is disassembled in the glove box and the diaphragm is taken out. After washing with DMC for 3 to 5 times, it is evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure are detected by ICP technology. The percentage is 3*10 -10 , recorded in Table 1
[0028] Example 2 - Na4Fe 0.695 Mn 1.75 V 0.3 Cr 0.05 Al 0.02 (PO4)2P2O7@C
[0029] The processes and conditions of other embodiments and comparative examples are the same as those of embodiment 1, except that:
[0030] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.0695 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.175 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.03 mol ammonium metavanadate NH4VO3, 0.005 mol chromium nitrate nonahydrate CrN3O9·9H2O, 0.002 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0031] 4) After heat treatment, the final product is obtained, which is recorded as sample 2#;
[0032] 5) Test sample 2# as follows:
[0033] a. The element ratio of Na:Fe:Mn:V:Cr:Al:P in ICP test is 4:0.695:1.75:0.3:0.05:0.02:4, which is Na4Fe 0.695 Mn 1.75 V 0.3 Cr 0.05 Al 0.02 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0034] c. The band gap width of the prepared sample 2# was tested by UV-visible absorption spectroscopy, and the test result was 3.35 eV;
[0035] d. The prepared sample 2# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 99.65%). From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 4μm-6μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0036] 6) Sample 2# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 1. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0037] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 0.55:0.695:1.75:0.3:0.05:0.02:4, that is, when charged to 4.5V, there are 3.45 reversible sodium ions in the structure for deintercalation;
[0038] b. The volume change of the unit cell during the charge and discharge process was analyzed by Re-fined-XRD technology, which was about 3%; 7) At the same time, the capacity retention rate of the battery after 200 cycles of 1C / 1C was 88%, which was recorded in Table 1. The battery was disassembled in the glove box and the diaphragm was taken out. After washing with DMC for 3-5 times, it was evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure were detected by ICP technology. The percentage was 4*10 -10 , recorded in Table 1
[0039] Example 3 - Na4Fe 0.5 Mn 1.75 V0.3 Cr 0.05 Al 0.15 (PO4)2P2O7@C
[0040] The processes and conditions of other embodiments and comparative examples are the same as those of embodiment 1, except that:
[0041] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.05 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.175 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.03 mol ammonium metavanadate NH4VO3, 0.005 mol chromium nitrate nonahydrate CrN3O9·9H2O, 0.015 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0042] 4) After heat treatment, the final product is obtained, which is recorded as sample 3#;
[0043] 5) Test sample 3# as follows:
[0044] a. The element ratio of Na:Fe:Mn:V:Cr:Al:P in ICP test is 4:0.5:1.75:0.3:0.05:0.15:4, which is Na4Fe 0.5 Mn 1.75 V 0.3 Cr 0.05 Al 0.15 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0045] c. The band gap width of the prepared sample 3# was tested by UV-visible absorption spectroscopy, and the test result was 3.5 eV;
[0046] d. The prepared sample 3# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 99.4%), and from SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 3μm-7μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0047] 6) Sample 3# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 1. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0048] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 0.85:0.5:1.75:0.3:0.05:0.15:4, that is, when charged to 4.5V, there are 3.15 reversible sodium ions in the structure for deintercalation;
[0049] b. The volume change of the unit cell during the charge and discharge process was analyzed by Re-fined-XRD technology, which was about 1.6%; 7) At the same time, the capacity retention rate of the battery after 200 cycles of 1C / 1C was 94%, which was recorded in Table 1. The battery was disassembled in the glove box and the diaphragm was taken out. After washing with DMC for 3-5 times, it was evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure were detected by ICP technology. The percentage was 2.5*10 -10 , recorded in Table 1
[0050] Example 4 - Na4Fe 0.68 Mn 1.75 V 0.3 Cr 0.02 Al 0.05 (PO4)2P2O7@C
[0051] The processes and conditions of other embodiments and comparative examples are the same as those of embodiment 1, except that:
[0052] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.068 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.175 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.03 mol ammonium metavanadate NH4VO3, 0.002 mol chromium nitrate nonahydrate CrN3O9·9H2O, 0.005 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0053] 4) After heat treatment, the final product is obtained, which is recorded as sample 4#;
[0054] 5) Test sample 4# as follows:
[0055] a. The element ratio of Na:Fe:Mn:V:Cr:Al:P in ICP test is 4:0.68:1.75:0.3:0.02:0.05:4, which is Na4Fe 0.68 Mn 1.75 V 0.3 Cr 0.02 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0056] c. The band gap width of the prepared sample 4# was tested by UV-visible absorption spectroscopy, and the test result was 3.4 eV;
[0057] d. XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test were performed on the prepared sample 4#. From XRD, it can be seen that the synthesized material is pure phase (purity is as high as 99.2%). From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 3μm-6μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability
[0058] 6) Sample 4# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 1. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0059] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 0.8:0.5:1.75:0.3:0.05:0.15:4, that is, when charged to 4.5V, there are 3.2 reversible sodium ions in the structure for deintercalation;
[0060] b. The volume change of the unit cell during the charge and discharge process was analyzed by Re-fined-XRD technology, which was about 2.3%; 7) At the same time, the capacity retention rate of the battery after 200 cycles of 1C / 1C was 90%, which was recorded in Table 1. The battery was disassembled in the glove box and the diaphragm was taken out. After washing with DMC for 3-5 times, it was evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure were detected by ICP technology. The percentage was 2.99*10 -10 , recorded in Table 1
[0061] Example 5 - Na4Fe0.5 Mn 1.75 V 0.3 Cr 0.15 Al 0.05 (PO4)2P2O7@C
[0062] The processes and conditions of other embodiments and comparative examples are the same as those of embodiment 1, except that:
[0063] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.05 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.175 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.03 mol ammonium metavanadate NH4VO3, 0.015 mol chromium nitrate nonahydrate CrN3O9·9H2O, 0.005 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0064] 4) After heat treatment, the final product is obtained, which is recorded as sample 5#;
[0065] 5) Test sample 5# as follows:
[0066] a. The element ratio of Na:Fe:Mn:V:Cr:Al:P in ICP test is 4:0.5:1.75:0.3:0.15:0.05:4, which is Na4Fe 0.5 Mn 1.75 V 0.3 Cr 0.15 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0067] c. The band gap width of the prepared sample 5# was tested by UV-visible absorption spectroscopy, and the test result was 3.2eV;
[0068] d. The prepared sample 5# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 99.2%). From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 2μm-4μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0069] 6) Sample 5# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 1. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0070] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 0.86:0.5:1.75:0.3:0.15:0.05:4, that is, when charged to 4.5V, there are 3.14 reversible sodium ions in the structure for deintercalation;
[0071] b. The volume change of the unit cell during the charge and discharge process was analyzed by Re-fined-XRD technology, which was about 2.2%; 7) At the same time, the capacity retention rate of the battery after 200 cycles of 1C / 1C was 89%, which was recorded in Table 1. The battery was disassembled in the glove box and the diaphragm was taken out. After washing with DMC for 3-5 times, it was evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure were detected by ICP technology. The percentage was 2.89*10 -10 , recorded in Table 1
[0072] Example 6Na4Fe 0.95 Mn 1.75 V 0.1 Cr 0.05 Al 0.05 (PO4)2P2O7@C
[0073] The processes and conditions of other embodiments and comparative examples are the same as those of embodiment 1, except that:
[0074] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.095 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.175 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.01 mol ammonium metavanadate NH4VO3, 0.005 mol chromium nitrate nonahydrate CrN3O9·9H2O, 0.005 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0075] 4) After heat treatment, the final product is obtained, which is recorded as sample 6#;
[0076] 5) Test sample 6# as follows:
[0077] a. The element ratio of Na:Fe:Mn:V:Cr:Al:P in ICP test is 4:0.95:1.75:0.1:0.05:0.05:4, which is Na4Fe 0.95 Mn 1.75 V 0.1 Cr 0.05 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0078] c. The band gap width of the prepared sample 6# was tested by UV-visible absorption spectroscopy, and the test result was 3.41 eV;
[0079] d. The prepared sample 6# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 99.5%). From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 1μm-5μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0080] 6) Sample 6# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 1. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0081] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 0.88:0.5:1.75:0.1:0.05:0.05:4, that is, when charged to 4.5V, there are 3.12 reversible sodium ions in the structure for deintercalation;
[0082] b. The volume change of the unit cell during the charge and discharge process was analyzed by Re-fined-XRD technology, which was about 3%; 7) At the same time, the capacity retention rate of the battery after 200 cycles of 1C / 1C was 91%, which was recorded in Table 1. The battery was disassembled in the glove box and the diaphragm was taken out. After washing with DMC for 3-5 times, it was evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure were detected by ICP technology. The percentage was 3.3*10 -10 , recorded in Table 1
[0083] Example 7Na4Fe0.5 Mn 1.75 V 0.4 Cr 0.05 Al 0.05 (PO4)2P2O7@C
[0084] The processes and conditions of other embodiments and comparative examples are the same as those of embodiment 1, except that:
[0085] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.05 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.175 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.04 mol ammonium metavanadate NH4VO3, 0.005 mol chromium nitrate nonahydrate CrN3O9·9H2O, 0.005 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0086] 4) After heat treatment, the final product is obtained, which is recorded as sample 7#;
[0087] 5) Test sample 7# as follows:
[0088] a. The element ratio of Na:Fe:Mn:V:Cr:Al:P in ICP test is 4:0.5:1.75:0.4:0.05:0.05:4, which is Na4Fe 0.5 Mn 1.75 V 0.4 Cr 0.05 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0089] c. The band gap width of the prepared sample 7# was tested by UV-visible absorption spectroscopy, and the test result was 3.21 eV;
[0090] d. The prepared sample 7# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 99.7%). From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 3μm-6μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0091] 6) Sample 7# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 1. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0092] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 0.67:0.5:1.75:0.4:0.05:0.05:4, that is, when charged to 4.5V, there are 3.33 reversible sodium ions in the structure for deintercalation;
[0093] b. The volume change of the unit cell during the charge and discharge process was analyzed by Re-fined-XRD technology, which was about 1.7%; 7) At the same time, the capacity retention rate of the battery after 200 cycles of 1C / 1C was 94%, which was recorded in Table 1. The battery was disassembled in the glove box and the diaphragm was taken out. After washing with DMC for 3-5 times, it was evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure were detected by ICP technology. The percentage was 2.9*10 -10 , recorded in Table 1
[0094] Example 8Na4Fe 0.85 Mn 1.55 V 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C
[0095] The processes and conditions of other embodiments and comparative examples are the same as those of embodiment 1, except that:
[0096] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.085 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.155 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.03 mol ammonium metavanadate NH4VO3, 0.005 mol chromium nitrate nonahydrate CrN3O9·9H2O, 0.005 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0097] 4) After heat treatment, the final product is obtained, which is recorded as sample 8#;
[0098] 5) Test sample 8# as follows:
[0099] a. The element ratio of Na:Fe:Mn:V:Cr:Al:P in ICP test is 4:0.85:1.55:0.3:0.05:0.05:4, which is Na4Fe 0.85 Mn 1.55 V 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0100] c. The band gap width of the prepared sample 8# was tested by UV-visible absorption spectroscopy, and the test result was 3.26 eV;
[0101] d. The prepared sample 8# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 99.5%). From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 4μm-8μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0102] 6) Sample 8# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 1. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0103] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 0.78:0.85:1.55:0.3:0.05:0.05:4, that is, when charged to 4.5V, there are 3.22 reversible sodium ions in the structure for deintercalation;
[0104] b. The Re-fined-XRD technique was used to analyze that the volume change of the unit cell during the charge and discharge process was about 1.65%;
[0105] 7) At the same time, the capacity retention rate of the battery after the above 1C / 1C cycle 200 times is 95%, which is recorded in Table 1. The battery is disassembled in the glove box and the diaphragm is taken out. After washing with DMC for 3-5 times, it is evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure are detected by ICP technology. The percentage is 2.1*10 -10 , recorded in Table 1
[0106] Example 9Na4Fe 0.3 Mn 2.1 V 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C
[0107] The processes and conditions of other embodiments and comparative examples are the same as those of embodiment 1, except that:
[0108] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.03 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.21 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.03 mol ammonium metavanadate NH4VO3, 0.005 mol chromium nitrate nonahydrate CrN3O9·9H2O, 0.005 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0109] 4) After heat treatment, the final product is obtained, which is recorded as sample 9#;
[0110] 5) Test sample 9# as follows:
[0111] a. The element ratio of Na:Fe:Mn:V:Cr:Al:P in ICP test is 4:0.3:2.1:0.3:0.05:0.05:4, which is Na4Fe 0.3 Mn 2.1 V 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0112] c. The band gap width of the prepared sample 9# was tested by UV-visible absorption spectroscopy, and the test result was 3.4 eV;
[0113] d. The prepared sample 9# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 99.8%). From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 3μm-8μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0114] 6) Sample 9# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 1. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0115] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 0.75:0.3:2.1:0.3:0.05:0.05:4, that is, when charged to 4.5V, there are 3.25 reversible sodium ions in the structure for deintercalation;
[0116] b. The volume change of the unit cell during the charge and discharge process was analyzed by Re-fined-XRD technology, which was about 3%; 7) At the same time, the capacity retention rate of the battery after 200 cycles of 1C / 1C was 90%, which was recorded in Table 1. The battery was disassembled in the glove box and the diaphragm was taken out. After washing with DMC for 3-5 times, it was evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure were detected by ICP technology. The percentage was 4.2*10 -10 , recorded in Table 1
[0117] Comparative Example
[0118] Comparative Example 1-Na4Fe 0.725 Mn 1.75 V 0.3 Cr 0.05 Al0(PO4)2P2O7@C
[0119] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.0725 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.175 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.03 mol ammonium metavanadate NH4VO3, 0.005 mol chromium nitrate nonahydrate CrN3O9·9H2O, stir until fully dissolved;
[0120] 2) Add 0.4 mol of sodium dihydrogen phosphate dihydrate NaH2PO4.2H2O (sodium source / phosphorus source) to the above aqueous solution, and continue stirring until the raw materials are completely dissolved to obtain a precursor solution;
[0121] 3) Pumping the precursor solution into a spray drying device protected by a nitrogen atmosphere for spray drying (inlet temperature of 160° C., outlet temperature of 95° C., feed flow rate of 60 ml / min, compressed nitrogen pressure of 0.8 KPa) to obtain a precursor powder;
[0122] 4) The precursor powder was then transferred into a high-temperature tube furnace protected by an argon atmosphere for heat treatment. The first stage heat treatment temperature was 400°C and the heat treatment time was 5 h. The second stage heat treatment temperature was 650°C and the heat treatment time was 10 h. The final product was obtained after heat treatment and was recorded as sample A#
[0123] 5) Test sample A# as follows:
[0124] a. Refined-XRD and ICP (main detection elements: Na / Fe / Mn / V / Cr / P) tests. Refined-XRD shows that the product after heat treatment is consistent with the crystal structure of Na4Fe3(PO4)2P2O7, belonging to the R3c space group. ICP test shows that the element ratio between Na:Fe:Mn:V:Cr:P is 4:0.725:1.75:0.3:0.05:4. Cr is distributed in the transition metal (Fe / Mn) position, that is, Na4Fe 0.7 Mn 1.75 V 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0125] b. XPS test was performed on the iron, manganese, vanadium and chromium elements in sample A#. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe 2+ , Mn 2+ 、V 3+ Cr 3+ ;
[0126] c. The band gap width of the prepared sample A# was tested by UV-visible absorption spectroscopy, and the test result was 3.6 eV;
[0127] d. The prepared sample A# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 98%), and from SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 3μm-5μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0128] 6) Sample A# was used as the active material, mixed evenly with the conductive agent acetylene black and the binder polyvinylidene fluoride in a mass ratio of 8:1:1, and an appropriate amount of solvent N-methylpyrrolidone was added to form a paste, which was applied on the aluminum current collector and cut into discs with a diameter of 14 mm after drying. The surface density of the active material was 1.1-3.2 mg / cm 2 (Here is 2.1 mg / cm 2 ), using this as the positive electrode of the battery, metallic sodium as the negative electrode, 1M NaClO4 / EC / DEC / 5%FEC (EC / DEC V / V=1:1) as the electrolyte, and a glass fiber membrane as the separator. The assembled battery was subjected to charge and discharge tests, and the charge and discharge cycles were performed 10 times under 0.2C / 0.2C conditions in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle were recorded in Table 1. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0129] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:P is 1.1:0.725:1.75:0.3:0.05:4, that is, when charged to 4.5V, there are 2.9 reversible sodium ions in the structure for deintercalation;
[0130] b. XPS test was performed on the iron, manganese, vanadium and chromium elements in the above-mentioned pole piece at the same time. The peak separation results showed that the iron and manganese in the above-mentioned pole piece were Fe 3+ , Mn 3+ 、V 5+ Cr 3+ , namely Fe 2+ / 3+ and Mn 2+ / 3+ A single electron transfer redox reaction occurs between them, and V 3 + / 5+ A two-electron transfer reaction occurs, and Cr 3+ No redox reaction occurs in the above process, that is, the number of electron transfers in the above process is > 1e - / valence-changing transition metal ions, the number of sodium ions undergoing redox deintercalation is > 3;
[0131] c. The Re-fined-XRD technique was used to analyze that the volume change of the unit cell during the charge and discharge process was about 5%; the inert sodium at the Na2 site participated in the redox insertion and extraction during the charge and discharge process, which realized the activation of the inert sodium ions in the unit cell structure;
[0132] 7) At the same time, the capacity retention rate of the battery after the above 1C / 1C cycle 200 times is 82%, which is recorded in Table 2. The battery is disassembled in the glove box and the diaphragm is taken out. After washing with DMC for 3-5 times, it is evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure are detected by ICP technology. The percentage is 7.5*10 -10 , recorded in Table 2
[0133] Comparative Example 2-Na4Fe 0.275 Mn 1.75 V 0.3 Cr 0.05 Al 0.3 (PO4)2P2O7@C
[0134] The processes and conditions of other comparative examples and comparative examples are the same as those of comparative example 1, except that:
[0135] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.0275 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.175 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.03 mol ammonium metavanadate NH4VO3, 0.005 mol chromium nitrate nonahydrate CrN3O9·9H2O, 0.03 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0136] 4) Recorded as sample B#
[0137] 5) Test sample B# as follows:
[0138] a. Refined-XRD and ICP (main detection elements: Na / Fe / Mn / V / Cr / Al / P) tests. Refined-XRD shows that the product after heat treatment is consistent with the crystal structure of Na4Fe3(PO4)2P2O7, belonging to the R3c space group. ICP test shows that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 4:0.275:1.75:0.3:0.05:0.3:4. Cr and Al are distributed in the transition metal (Fe / Mn) position, that is, Na4Fe 0.275 Mn 1.75 V 0.3 Cr 0.05 Al 0.3 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0139] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in sample B#. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe 2+ , Mn 2+ 、V 3+ Cr 3+ 、Al 3+ ;
[0140] c. The band gap width of the prepared sample B# was tested by UV-visible absorption spectroscopy, and the test result was 3.7 eV;
[0141] d. The prepared sample B# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 97%), and from SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 4μm-10μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0142] 6) Sample B# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 2. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0143] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 1.25:0.275:1.75:0.3:0.05:0.3:4, that is, when charged to 4.5V, there are 2.75 reversible sodium ions in the structure for deintercalation;
[0144] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in the above-mentioned pole piece at the same time. The peak separation results showed that the iron and manganese in the above-mentioned pole piece were Fe 3+ , Mn 3+ 、V 5+ Cr 3+ 、Al 3+ , namely Fe 2+ / 3+ and Mn 2+ / 3+ A single electron transfer redox reaction occurs between them, and V 3+ / 5+ A two-electron transfer reaction occurs, and Cr 3+ 、Al 3+ No redox reaction occurs in the above process, that is, the number of electron transfers in the above process is > 1e - / variable valence transition metal ions, the number of sodium ions undergoing redox deintercalation>3; c. The volume change of the unit cell during the charge and discharge process was analyzed by Re-fined-XRD technology to be about 3%; 7) At the same time, the capacity retention rate of the battery after the above 1C / 1C cycle 200 times was 86%, which is recorded in Table 1, and the battery was disassembled in the glove box and the diaphragm was taken out, and after being cleaned with DMC for 3-5 times, it was evaporated in the glove box, and the mass of manganese dissolved on the diaphragm was detected by ICP technology. The percentage of the mass of manganese in the positive electrode structure is 4*10 -10 , recorded in Table 2
[0145] Comparative Example 3-Na4Fe 0.725 Mn 1.75 V 0.3 Cr0Al 0.05 (PO4)2P2O7@C
[0146] The processes and conditions of other comparative examples and comparative examples are the same as those of comparative example 1, except that:
[0147] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.0725 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.175 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.03 mol ammonium metavanadate NH4VO3, 0.005 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0148] 4) Record as sample C#
[0149] 5) Test sample C# as follows:
[0150] a. Refined-XRD and ICP (main detection elements: Na / Fe / Mn / V / Al / P) tests. Refined-XRD shows that the product after heat treatment is consistent with the crystal structure of Na4Fe3(PO4)2P2O7, belonging to the R3c space group, with Al distributed in the transition metal (Fe / Mn) position. ICP test shows that the element ratio between Na:Fe:Mn:V:Al:P is 4:0.725:1.75:0.3:0.05:4, which is Na4Fe 0.725 Mn 1.75 V 0.3 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure; b. XPS test of iron, manganese, vanadium and aluminum elements in sample C#. The peak separation results show that the iron and manganese in the above-mentioned electrode are Fe2+ , Mn 2+ 、V 3+ 、Al 3+ ;
[0151] c. The band gap width of the prepared sample C# was tested by UV-visible absorption spectroscopy, and the test result was 3.4 eV;
[0152] d. The prepared sample C# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 98%). From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 4μm-8μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0153] 6) Sample C# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 2. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0154] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Al:P is 1.09:0.725:1.75:0.3:0.05:4, that is, when charged to 4.5V, there are 2.91 reversible sodium ions in the structure for deintercalation;
[0155] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in the above-mentioned pole piece at the same time. The peak separation results showed that the iron and manganese in the above-mentioned pole piece were Fe 3+ , Mn 3+ 、V 5+ 、Al 3+ , namely Fe 2+ / 3+ and Mn 2+ / 3+ A single electron transfer redox reaction occurs between them, and V 3+ / 5+ Two electron transfer reactions occurred, and Al 3+ No redox reaction occurs in the above process, that is, the number of electron transfers in the above process is > 1e - / valence-changing transition metal ions, the number of sodium ions undergoing redox deintercalation is > 3;
[0156] c. The volume change of the unit cell during the charge and discharge process was analyzed by Re-fined-XRD technology, which was about 4%; 7) At the same time, the capacity retention rate of the battery after 200 cycles of 1C / 1C was 85%, which was recorded in Table 1. The battery was disassembled in the glove box and the diaphragm was taken out. After washing with DMC for 3-5 times, it was evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure were detected by ICP technology. The percentage was 3.5*10 -10 , recorded in Table 2
[0157] Comparative Example 4-Na4Fe 0.275 Mn 1.75 V 0.3 Cr 0.3 Al 0.05 (PO4)2P2O7@C
[0158] The processes and conditions of other embodiments and comparative examples are the same as those of Comparative Example 1, except that:
[0159] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.0275 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.175 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.03 mol ammonium metavanadate NH4VO3, 0.03 mol chromium nitrate nonahydrate CrN3O9·9H2O, 0.005 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0160] 4) Recorded as sample D#
[0161] 5) Test sample D# as follows:
[0162] a. Refined-XRD and ICP (main detection elements: Na / Fe / Mn / V / Cr / Al / P) tests. Refined-XRD shows that the product after heat treatment is consistent with the crystal structure of Na4Fe3(PO4)2P2O7, belonging to the R3c space group. ICP test shows that the element ratio between Na:Fe:Mn:V:Al:P is 4:0.275:1.75:0.3:0.3:0.05:4. Cr and Al are distributed in the transition metal (Fe / Mn) position, that is, Na4Fe 0.275 Mn 1.75 V 0.3 Cr 0.3 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0163] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in sample D#. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe 2+ , Mn 2+ 、V 3+ Cr 3+ 、Al 3+ ;
[0164] c. The band gap width of the prepared sample D# was tested by UV-visible absorption spectroscopy, and the test result was 3.6 eV;
[0165] d. The prepared sample D# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 97%), and from SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 4μm-8μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0166] 6) Sample D# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 1. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0167] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 1.3:0.275:1.75:0.3:0.3:0.05:4, that is, when charged to 4.5V, there are 2.7 reversible sodium ions in the structure for deintercalation;
[0168] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in the above-mentioned pole piece at the same time. The peak separation results showed that the iron and manganese in the above-mentioned pole piece were Fe 3+ , Mn 3+ 、V 5+ 、Al 3+ , namely Fe 2+ / 3+ and Mn 2+ / 3+ A single electron transfer redox reaction occurs between them, and V 3+ / 5+ Two electron transfer reactions occurred, and Al 3+ No redox reaction occurs in the above process, that is, the number of electron transfers in the above process is > 1e - / valence-changing transition metal ions, the number of sodium ions undergoing redox deintercalation is > 3;
[0169] c. The volume change of the unit cell during the charge and discharge process was analyzed by Re-fined-XRD technology, which was about 4.2%; 7) At the same time, the capacity retention rate of the battery after 200 cycles of 1C / 1C was 84%, which was recorded in Table 2. The battery was disassembled in the glove box and the diaphragm was taken out. After washing with DMC for 3-5 times, it was evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure were detected by ICP technology. The percentage was 3.4*10 -10 , recorded in Table 2.
[0170] Comparative Example 5-Na4Fe 1.1 Mn 1.75 V0Cr 0.05 Al 0.05 (PO4)2P2O7@C
[0171] The processes and conditions of other comparative examples and comparative examples are the same as those of comparative example 1, except that:
[0172] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.11 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.175 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.005 mol chromium nitrate nonahydrate CrN3O9·9H2O, 0.005 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0173] 4) Recorded as sample E#
[0174] 5) Test sample E# as follows:
[0175] a. Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Cr / Al / P) tests. Refined-XRD shows that the product after heat treatment is consistent with the crystal structure of Na4Fe3(PO4)2P2O7, belonging to the R3c space group. ICP test shows that the element ratio between Na:Fe:Mn:V:Al:P is 4:1.1:1.75:0.05:0.05:4. Cr and Al are distributed in the transition metal (Fe / Mn) position, that is, Na4Fe 1.1 Mn 1.75 Cr 0.05 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure; b. XPS test of iron, manganese, chromium and aluminum elements in sample E#, the peak separation results show that the iron and manganese in the above-mentioned electrode are Fe 2+ , Mn2+ Cr 3+ 、Al 3 + ;
[0176] c. The band gap width of the prepared sample E# was tested by UV-visible absorption spectroscopy, and the test result was 3.7 eV;
[0177] d. The prepared sample E# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 97.5%), and from SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 4μm-8μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0178] 6) Sample E# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 2. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0179] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:Cr:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:Cr:Al:P is 1.1:1.1:1.75:0.05:0.05:4, that is, when charged to 4.5V, there are 2.9 reversible sodium ions in the structure for deintercalation;
[0180] b. XPS test was performed on the iron, manganese, chromium and aluminum elements in the above-mentioned pole piece at the same time. The peak separation results showed that the iron and manganese in the above-mentioned pole piece were Fe 3+ , Mn 3+ Cr 3+ 、Al 3+ , namely Fe 2+ / 3+ and Mn 2+ / 3+ A single electron transfer redox reaction occurs between the 3+ ,Cr 3+ No redox reaction occurs in the above process, that is, the number of electron transfer in the above process is about 1e - / variable valence transition metal ions, the number of sodium ions undergoing redox deintercalation is about 3;
[0181] c. The volume change of the unit cell during the charge and discharge process was analyzed by Re-fined-XRD technology, which was about 6%; 7) At the same time, the capacity retention rate of the battery after 200 cycles of 1C / 1C was 80%, which was recorded in Table 1. The battery was disassembled in the glove box and the diaphragm was taken out. After washing with DMC for 3-5 times, it was evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure were detected by ICP technology. The percentage was 6*10 -10 , recorded in Table 2.
[0182] Comparative Example 6-Na4Fe 0.35 Mn 1.75 V 0.5 Cr 0.05 Al 0.05 (PO4)2P2O7@C
[0183] The processes and conditions of other comparative examples and comparative examples are the same as those of comparative example 1, except that:
[0184] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.035 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.175 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.05 mol ammonium metavanadate NH4VO3, 0.005 mol chromium nitrate nonahydrate CrN3O9·9H2O, 0.005 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0185] 4) Recorded as sample F#
[0186] 5) Test sample F# as follows:
[0187] a. Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Cr / V / Al / P) tests. Refined-XRD shows that the product after heat treatment is consistent with the crystal structure of Na4Fe3(PO4)2P2O7, belonging to the R3c space group. ICP test shows that the element ratio between Na:Fe:Mn:V:Al:P is 4:0.35:1.75:0.5:0.05:0.05:4. Cr and Al are distributed in the transition metal (Fe / Mn) position, that is, Na4Fe 0.35 Mn 1.75 V 0.5 Cr 0.05 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0188] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in sample F#. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe 2+ , Mn 2+ 、V 3+ Cr 3+ 、Al 3+ ;
[0189] c. The band gap width of the prepared sample F# was tested by UV-visible absorption spectroscopy, and the test result was 3.6 eV;
[0190] d. The prepared sample F# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 98%). From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 5μm-8μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0191] 6) Sample F# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 2. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0192] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 0.69:0.35:1.75:0.5:0.05:0.05:4, that is, when charged to 4.5V, there are 2.8 reversible sodium ions in the structure for deintercalation;
[0193] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in the above-mentioned pole piece at the same time. The peak separation results showed that the iron and manganese in the above-mentioned pole piece were Fe 3+ , Mn 3+ 、V 5+ Cr 3+ 、Al 3+ , namely Fe 2+ / 3+ and Mn 2+ / 3+ A single electron transfer redox reaction occurs between the 3+ ,Cr 3+ No redox reaction occurs in the above process, that is, the number of electron transfers in the above process is > 1e - / valence-changing transition metal ions, the number of sodium ions undergoing redox deintercalation is > 3;
[0194] c. The volume change of the unit cell during the charge and discharge process was analyzed by Re-fined-XRD technology, which was about 5%; 7) At the same time, the capacity retention rate of the battery after 200 cycles of 1C / 1C was 88%, which was recorded in Table 1. The battery was disassembled in the glove box and the diaphragm was taken out. After washing with DMC for 3-5 times, it was evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure were detected by ICP technology. The percentage was 4.8*10 -10 , recorded in Table 2.
[0195] Comparative Example 7 - Na4Fe1Mn 1.4 V 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C
[0196] The processes and conditions of other comparative examples and comparative examples are the same as those of comparative example 1, except that:
[0197] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.1 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.14 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.03 mol ammonium metavanadate NH4VO3, 0.005 mol chromium nitrate nonahydrate CrN3O9·9H2O, 0.005 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0198] 4) Recorded as sample G#
[0199] 5) Test sample G# as follows:
[0200] a. Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Cr / V / Al / P) tests. Refined-XRD shows that the product after heat treatment is consistent with the crystal structure of Na4Fe3(PO4)2P2O7, belonging to the R3c space group. ICP test shows that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 4:1:1.4:0.3:0.05:0.05:4. Cr and Al are distributed in the transition metal (Fe / Mn) position, that is, Na4Fe1Mn 1.4 V 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0201] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in sample G#. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe 2+ , Mn 2+ 、V 3+ Cr 3+ 、Al 3+ ;
[0202] c. The band gap width of the prepared sample F# was tested by UV-visible absorption spectroscopy, and the test result was 3.4 eV;
[0203] d. The prepared sample G# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 97%). From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 3μm-8μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0204] 6) Sample G# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 2. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0205] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 0.97:1:1.4:0.3:0.05:0.05:4, that is, when charged to 4.5V, there are 3.03 reversible sodium ions in the structure for deintercalation;
[0206] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in the above-mentioned pole piece at the same time. The peak separation results showed that the iron and manganese in the above-mentioned pole piece were Fe 3+ , Mn 3+ 、V 5+ Cr 3+ 、Al 3+ , namely Fe 2+ / 3+ and Mn 2+ / 3+ A single electron transfer redox reaction occurs between the 3+ ,Cr 3+ No redox reaction occurs in the above process, that is, the number of electron transfers in the above process is > 1e - / valence-changing transition metal ions, the number of sodium ions undergoing redox deintercalation is > 3;
[0207] c. The volume change of the unit cell during the charge and discharge process was analyzed by Re-fined-XRD technology, which was about 5%; 7) At the same time, the capacity retention rate of the battery after 200 cycles of 1C / 1C was 88%, which was recorded in Table 1. The battery was disassembled in the glove box and the diaphragm was taken out. After washing with DMC for 3-5 times, it was evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure were detected by ICP technology. The percentage was 5*10 -10 , recorded in Table 2.
[0208] Comparative Example 8-Na4Fe 1.4 Vt 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C
[0209] The processes and conditions of other comparative examples and comparative examples are the same as those of comparative example 1, except that:
[0210] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.14 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.1 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.03 mol ammonium metavanadate NH4VO3, 0.005 mol chromium nitrate nonahydrate CrN3O9·9H2O, 0.005 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0211] 4) Recorded as sample H#
[0212] 5) Test sample H# as follows:
[0213] a. Refined-XRD and ICP (main detection elements: Na / Fe / Mn / Cr / V / Al / P) tests. Refined-XRD shows that the product after heat treatment is consistent with the crystal structure of Na4Fe3(PO4)2P2O7, belonging to the R3c space group. ICP test shows that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 4:1.4:1:0.3:0.05:0.05:4. Cr and Al are distributed in the transition metal (Fe / Mn) position, that is, Na4Fe 1.4 Vt 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0214] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in sample H#. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe 2+ , Mn 2+ 、V 3+ Cr 3+ 、Al 3+ ;
[0215] c. The band gap width of the prepared sample H# was tested by UV-visible absorption spectroscopy, and the test result was 3.6 eV;
[0216] d. The prepared sample H# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 97.2%). From SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 2μm-7μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0217] 6) Sample H# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 2. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0218] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:Al:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 0.99:1.4:1:0.3:0.05:0.05:4, that is, when charged to 4.5V, there are 3.01 reversible sodium ions in the structure for deintercalation;
[0219] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in the above-mentioned pole piece at the same time. The peak separation results showed that the iron and manganese in the above-mentioned pole piece were Fe 3+ , Mn 3+ 、V 5+ Cr 3+ 、Al 3+ , namely Fe 2+ / 3+ and Mn 2+ / 3+ A single electron transfer redox reaction occurs between the 3+ ,Cr 3+ No redox reaction occurs in the above process, that is, the number of electron transfers in the above process is > 1e - / valence-changing transition metal ions, the number of sodium ions undergoing redox deintercalation is > 3;
[0220] c. The volume change of the unit cell during the charge and discharge process was analyzed by Re-fined-XRD technology, which was about 4%; 7) At the same time, the capacity retention rate of the battery after 200 cycles of 1C / 1C was 86%, which was recorded in Table 1. The battery was disassembled in the glove box and the diaphragm was taken out. After washing with DMC for 3-5 times, it was evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure were detected by ICP technology. The percentage was 4*10 -10 , recorded in Table 2.
[0221] Comparative Example 9-Na4Fe 0.65 Mn 1.75 V 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C
[0222] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.065 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.175 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.03 mol ammonium metavanadate NH4VO3, 0.005 mol chromium nitrate nonahydrate CrN3O9·9H2O, stir until fully dissolved, 0.005 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0223] 4) Recorded as sample K#
[0224] 5) Test sample K# as follows:
[0225] a. Refined-XRD and ICP (main detection elements: Na / Fe / Mn / V / Cr / Al / P) tests. Refined-XRD shows that the product after heat treatment is consistent with the crystal structure of Na4Fe3(PO4)2P2O7, belonging to the R3c space group. ICP test shows that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 4:0.65:1.75:0.3:0.05:0.05:4. Cr and Al are distributed in the transition metal (Fe / Mn) position, that is, Na4Fe 0.65 Mn 1.75 V 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0226] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in sample K#. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe 2+ , Mn 2+ 、V 3+ Cr 3+ 、Al 3+ ;
[0227] c. The band gap width of the prepared sample K# was tested by UV-visible absorption spectroscopy, and the test result was 3.5 eV;
[0228] d. The prepared sample K# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 96.8%), and from SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 8μm-10μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0229] 2) Sample K# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 2. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0230] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:P is 1:0.65:1.75:0.3:0.05:0.05:4, that is, when charged to 4.5V, there are 3 reversible sodium ions in the structure for deintercalation;
[0231] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in the above-mentioned pole piece at the same time. The peak separation results showed that the iron and manganese in the above-mentioned pole piece were Fe 3+ , Mn 3+ 、V 4+ Cr 3+ 、Al 3+ , namely Fe 2+ / 3+ and Mn 2+ / 3+ A single electron transfer redox reaction occurs between them, and V 3+ / 4+ A single electron transfer reaction occurs, and Cr 3+ 、Al 3+ No redox reaction occurs in the above process, that is, the number of electron transfer in the above process is about 1e - / variable valence transition metal ions, the number of sodium ions undergoing redox deintercalation is about 3; c. The volume change of the unit cell during the charge and discharge process is analyzed by Re-fined-XRD technology to be about 8%; 7) At the same time, the capacity retention rate of the battery after the above 1C / 1C cycle 200 times is 80%, which is recorded in Table 1, and the battery is disassembled in the glove box and the diaphragm is taken out, and after being cleaned with DMC for 3-5 times, it is evaporated in the glove box, and the mass of manganese dissolved on the diaphragm is detected by ICP technology. The percentage of the mass of manganese in the positive electrode structure is 7*10 -10 , recorded in Table 2
[0232] Comparative Example 10-Na4Fe 0.65 Mn 1.75 V 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C
[0233] 1) Add 500 mL of deionized water to a beaker, heat it in a water bath to 60°C, and add 0.3 mol of citric acid monohydrate, C6H 10 O8, 0.3 mol ethylene glycol C2H6O2, 0.065 mol iron nitrate nonahydrate FeN3O9·9H2O, 0.175 mol manganese nitrate tetrahydrate MnN2O6·4H2O, 0.03 mol ammonium metavanadate NH4VO3, 0.005 mol chromium nitrate nonahydrate CrN3O9·9H2O, stir until fully dissolved, 0.005 mol aluminum nitrate nonahydrate AlN3O9·9H2O, stir until fully dissolved;
[0234] 4) Recorded as sample L#
[0235] 5) Test sample L# as follows:
[0236] a. Refined-XRD and ICP (main detection elements: Na / Fe / Mn / V / Cr / Al / P) tests. Refined-XRD shows that the product after heat treatment is consistent with the crystal structure of Na4Fe3(PO4)2P2O7, belonging to the R3c space group. ICP test shows that the element ratio between Na:Fe:Mn:V:Cr:Al:P is 4:0.65:1.75:0.3:0.05:0.05:4. Cr and Al are distributed in the transition metal (Fe / Mn) position, that is, Na4Fe 0.65 Mn 1.75 V 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C material, which is consistent with the Refined-XRD structure;
[0237] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in sample L#. The peak separation results showed that the iron and manganese in the above-mentioned electrode were Fe 2+ , Mn 2+ 、V 3+ Cr 3+ 、Al 3+ ;
[0238] c. The band gap width of the prepared sample K# was tested by UV-visible absorption spectroscopy, and the test result was 3.63 eV;
[0239] d. The prepared sample L# was subjected to XRD, SEM characterization, carbon content (TG) test and button half-cell charge and discharge cycle test. From XRD, it can be seen that the synthesized material is pure phase (purity up to 97%), and from SEM, it can be seen that the particle size is uniform and the particle size is small, with a particle size of 8μm-15μm. From the button half-cell 1C charge and discharge cycle test, it can be seen that the positive electrode material has good cycle stability.
[0240] 2) Sample L# was used as the active material, and the charge and discharge cycle was performed 10 times at 0.2C / 0.2C in the voltage range of 1.5V-4.5V. The data of the discharge specific capacity of the stable cycle was recorded in Table 2. The battery was then charged to 4.5V and then cut off. The positive electrode sheet was disassembled from the battery in a glove box, washed with DMC for 3-5 times, and then evaporated to dryness in the glove box;
[0241] a. Take part of the electrode for ICP test (main detection elements: Na:Fe:Mn:V:Cr:P). The ICP test results show that the element ratio between Na:Fe:Mn:V:Cr:P is 1.02:0.65:1.75:0.3:0.05:0.05:4, that is, when charged to 4.5V, there are 2.98 reversible sodium ions in the structure for deintercalation;
[0242] b. XPS test was performed on the iron, manganese, vanadium, chromium and aluminum elements in the above-mentioned pole piece at the same time. The peak separation results showed that the iron and manganese in the above-mentioned pole piece were Fe 3+ , Mn 3+ 、V 4+ Cr 3+ 、Al 3+ , namely Fe 2+ / 3+ and Mn 2+ / 3+ A single electron transfer redox reaction occurs between V 3+ / 4+ A single electron transfer reaction occurs, and Cr 3+ 、Al 3+ No redox reaction occurs in the above process, that is, the number of electron transfer in the above process is about 1e - / variable valence transition metal ions, the number of sodium ions undergoing redox deintercalation is about 3; c. The volume change of the unit cell during the charge and discharge process is analyzed by Re-fined-XRD technology, which is about 10%; 7) At the same time, the capacity retention rate of the battery after 200 cycles of 1C / 1C is 79%, which is recorded in Table 1, and the battery is disassembled in the glove box and the diaphragm is taken out. After washing with DMC for 3-5 times, it is evaporated in the glove box. The mass of manganese dissolved on the diaphragm and the mass of manganese in the positive electrode structure are detected by ICP technology. The percentage is 8*10 -10 , recorded in Table 2
[0243] Example (Table 1)
[0244]
[0245] Comparative Example (Table 2)
[0246]
[0247] in conclusion
[0248] The present invention provides a new structure of phosphate-pyrophosphate composite polyanion compound and its preparation method. By precisely controlling the ratio of iron, manganese, vanadium and transition metal ions, the redox potential of the material is improved, the ionic conductivity and electronic conductivity of the material are improved, and the unit cell structure is stabilized. This further improves the actual gram capacity, rate performance and cycle stability of the material in the process of application as a positive electrode material for sodium ion batteries. The prepared Na4Fe 0.65 Mn 1.75 V 0.3 Cr 0.05 Al 0.05 (PO4)2P2O7@C, the discharge capacity at 0.2C can reach 156mAh / g, and the median voltage is 3.7V. The discharge capacity at 1C is 122mAh / g, and the discharge capacity at 5C is 109mAh / g. The capacity retention rate is as high as 90% after 200 cycles of charge and discharge at 1C.
[0249] The doping of transition metal sites (iron, manganese, vanadium) in the unit cell structure has a great influence on improving the ionic conductivity and electronic conductivity of the material, stabilizing the unit cell structure, and reducing the bandgap width of the material. 3+ (including unpaired electrons), Al 3+(Al-O covalent bonds stabilize the unit cell structure) can help the inert sodium ions in the structure to undergo reversible electrochemical deintercalation / embedding, achieving a multi-electron transfer process of more than three electrons, thereby improving the material's specific capacity and cycle stability. However, excessive transition metal site doping will reduce the redox active sites in the electrochemical process, resulting in a decrease in specific capacity. Through the examples and comparative examples of the present invention, it is found that when Na4Fe 3-x-1.5y-z Mn x V y A z In the (PO4)2P2O7@C structure, x is 1.75, y is 0.3, and when the z value satisfies 0.25≥z≥0.1, the prepared material has excellent rate performance and capacity retention rate, and the discharge capacity can reach 137-156mAh / g at 0.2C, the median voltage is 3.52V-3.7V, the discharge capacity can reach 109-122mAh / g at 1C, and the discharge capacity can reach 100-109mAh / g at 5C. The capacity retention rate is as high as 89%-94% after 200 charge and discharge cycles at 1C. (Such as: Examples 1-4, Comparative Examples 1-4)
[0250] When the ratio of doping elements is fixed, the ratio of the three active transition metal ions of iron, manganese and vanadium has a significant effect on the electrochemical behavior of the material, thereby affecting the rate performance of the material and the capacity retention rate under cycling conditions. 3-x-1.5y-z Mn x V y A z In the (PO4)2P2O7@C structure, x is 1.75, z is 0.2, and when the y value satisfies 0.5≥y≥0.1, the prepared material has excellent rate performance and capacity retention rate. The discharge capacity can reach 135-150mAh / g at 0.2C, the median voltage is 3.43V-3.52V, the discharge capacity can reach 108-119mAh / g at 1C, and the discharge capacity can reach 100-111mAh / g at 5C. The capacity retention rate is as high as 89%-94% after 200 charge and discharge cycles at 1C. (For example: Examples 6-8, Comparative Examples 5-6) When Na4Fe 3-x-1.5y-z Mn x V y A zIn the (PO4)2P2O7@C structure, y is 0.3, z is 0.2, and when the x value satisfies 2.25≥x≥1.5, the prepared material has excellent rate performance and capacity retention rate, the discharge capacity can reach 140-142mAh / g at 0.2C, the median voltage is 3.40V-3.65V, the discharge capacity can reach 112-117mAh / g at 1C, and the discharge capacity can reach 105-108mAh / g at 5C. The capacity retention rate is as high as 90%-95% after 200 charge and discharge cycles at 1C. (such as: Examples 9-10, Comparative Examples 7-8)
[0251] When Na4Fe 3-x-1.5y-z Mn x V y A z When x, y, and z are boundary conditions in the (PO4)2P2O7@C structure, the performance of the prepared material needs to be further improved. (eg: Examples 5-8)
[0252] When Na4Fe 3-x-1.5y-z Mn x V y A z When the x, y, and z compositions in the (PO4)2P2O7@C structure are the same and the carbon source is a macromolecular network carbon structure, the prepared material has excellent rate performance and capacity retention rate. The discharge capacity per gram at 0.2C can reach 135-156 mAh / g, the median voltage is 3.40V-3.7V, the discharge capacity per gram at 1C can reach 108-122 mAh / g, and the discharge capacity per gram at 5C can reach 105-111 mAh / g. The capacity retention rate after 200 charge and discharge cycles at 1C is as high as 89%-95% (such as: Examples 1-9). However, the above effects cannot be achieved when a single carbon source is used alone (such as: Comparative Examples 9-10).
Claims
1. A phosphate pyrophosphate composite polyanionic compound, characterized in that: The phosphate pyrophosphate composite polyanionic compound has a structure shown in Formula I: Na4Fe 3-x-1.5y-z Mn x V y A z (PO4)2P2O7@C Formula I 1) The phosphate pyrophosphate composite polyanionic compound: when having the structure shown in Formula I: 1.5<x<2.8, preferably 1.75≤x≤2.4; 0<y<0.5, preferably 0.15≤x≤0.35; 0<z<0.3, preferably 0.02≤x≤0.1; 2) A is selected from Mg 2+ 、Al 3+ Cr 3+ , Ga 3+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ ,Ge 2+ 、Zr 4+ , Nb 3+ / 4+ 、Mo 3+ 、In 3+ Sn 4+ , Sb 3 + 、Te 4+ 、Ce 4+ , Pr 4+ 、Nd 3+ 、Pm 3+ 、 3+ / 4+ , W 4+ 、Bi 5+ 、Po 6+ , Cm 4+ , Bk 4+ 1 or more of the following: More preferably, Mg 2+ 、Al 3+ Cr 3+ , Ga 3+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ ,Ge 2+ 、Zr 4+ , Nb 3+ / 4+ 、Mo 3+ 、In 3+ Sn 4 + , Sb 3+ 、Ce 4+ 、Nd 3+ 、 3+ / 4+ , W 4+ 、Bi 5+ 1 or more of the following; 3) x, y, and z should ensure that the phosphate-pyrophosphate complex polyanionic compound designed in formula I is electrically neutral.
2. The phosphate pyrophosphate composite polyanionic compound according to claim 1, characterized in that The mass content of C is 1wt%-12wt%, and more preferably 3wt%-8wt%; x, y, and z should ensure that the phosphate-pyrophosphate composite polyanionic compound designed in formula I is electrically neutral, that is, it satisfies the following relationship: When A is selected from Mg 2+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ ,Ge 2+ , it is necessary to satisfy 4+2*(3-x-1.5yz)+x+y+z)=10; When A is selected from Al 3+ Cr 3+ , Ga 3+ , Nb 3+ 、Mo 3+ 、In 3+ 、Nd 3+ 、Pm 3+ 、 3+ , it is necessary to satisfy 4+2*(3-x-1.5yz)+x+y+)+3z=10; When A is selected from Zr 4+ , Nb 4+ Sn 4+ 、Te 4+ 、Ce 4+ , Pr 4+ 、 4+ , W 4+ , Cm 4+ , Bk 4+ When , it is necessary to satisfy 4+2*(3-x-1.5yz)+x+y+)+4z=10; When A is selected from Bi 5+ Medium, 4+2*(3-x-1.5yz)+x+y+)+5z=10; When A is selected from Po 6+ In, 4+2*(3-x-1.5yz)+x+y+)+6z=10.
3. A method for preparing the phosphate pyrophosphate composite polyanionic compound according to claim 1 or 2, characterized in that: The specific steps include: Step 1), using one or more of a solid phase calcination method, a sol-gel method, and a solvothermal method, a sodium source, an iron source, a manganese source, a vanadium source, an A source, a phosphorus source, a carbon source, and a reducing agent are mixed to obtain a solid substance; The mixing method is one or more of ball milling, jar milling, sand milling, water dissolution, mechanical stirring, melting, etc.; Step 2), heat-treating the solid material obtained in step 1); the solid material must be processed by crushing, ball milling, pot milling, etc. before heat treatment to be in a powder state; Preferably, the temperature T1 is 300<T1<450℃, and the treatment time is 0.5-10h; the temperature T2 is 450<T2<700℃, and the treatment time is 3-20h; The heat treatment is carried out under a specific flowing atmosphere, and the specific atmosphere is selected from an inert atmosphere including one or more of argon, nitrogen, and helium, or an inert atmosphere gas containing a hydrogen volume concentration greater than 0 and less than 20%.
4. The method for preparing the compound according to claim 3, characterized in that: The solid phase calcination method described in step 1) comprises the following process: The sodium source, the iron source, the manganese source, the vanadium source, the A source, the phosphorus source, the carbon source and the reducing agent are uniformly mixed to obtain a solid precursor; When insoluble raw materials exist in the sodium source, iron source, manganese source, vanadium source, A source, phosphorus source, carbon source and reducing agent, the mixing method is one or more of ball milling, jar milling or sand milling, and a solvent needs to be added during mixing to obtain a precursor slurry, the solvent is water, ethanol, or a mixed solvent of water and ethanol, the mass of water in the mixed solvent preferably accounts for (30-80) wt%, more preferably (45-55) wt%, the mass of ethanol accounts for (20-70) wt%, more preferably (45-55) wt%, when the particle size range of the precursor slurry is 0.5 μm-1.0 μm, the precursor slurry is pumped into the atomizer of the spray dryer by a peristaltic pump, and the powder is collected; after the precursor slurry is dried, a solid precursor with a particle size of 20 μm-30 μm is obtained; When there is no insoluble raw material in the sodium source, iron source, manganese source, vanadium source, A source, phosphorus source, carbon source, and reducing agent, when the mixing method is dissolution, a solvent needs to be added to the mixing to obtain a precursor solution, and the solvent is water. The precursor solution is pumped into the atomizer of the spray dryer through a peristaltic pump to collect powder; after the precursor slurry is dried, a solid precursor with a particle size of 20μm-30μm is obtained; When the sodium source, iron source, manganese source, vanadium source, A source, phosphorus source, carbon source and reducing agent are mixed in a melting manner, the raw materials are placed in a graphite crucible, and the temperature is rapidly raised to a temperature at which the raw materials are in a fluid state, and the temperature is maintained for 0.5-1h, and then rapidly cooled to room temperature in 2-5min to obtain a molten raw material; the molten raw material is ball-milled to obtain a solid precursor, and the particle size of the solid precursor is 25μm-35μm; the ball milling speed is 300r / min-800r / min, and more preferably 400r / min-500r / min; the ball milling time is 2h-8h, and more preferably 3.5h-5h; The spray drying is preferably controlled such that the feed flow rate is 20 mL / min to 60 mL / min, the air inlet temperature is 120°C to 195°C, the air outlet temperature is 80°C to 110°C, and the compressed air pressure is 0.03 KPa to 0.9 KPa. The precursor slurry is pumped into the atomizer of the spray dryer through a peristaltic pump to collect the powder. After the precursor slurry is dried, a precursor powder with a particle size of 20 μm to 30 μm is obtained. Or, the sol-gel method described in step 1) includes the following process: When there is no insoluble raw material in the sodium source, iron source, manganese source, vanadium source, A source, phosphorus source, carbon source and reducing agent, when the mixing method is selected as water dissolution, a solvent needs to be added to the mixture to obtain a precursor solution, the solvent is water, and the precursor solution is evaporated by water bath heating to a gel state and then transferred to a blast drying oven for drying; the water bath heating temperature is 65°C-95°C, more preferably 80°C-90°C; the drying temperature is 70°C-120°C, more preferably 85°C-100°C; the solid obtained after drying is ground or ball-milled into a powder state to obtain a solid precursor with a particle size of 25μm-35μm; the ball milling speed is 300r / min-800r / min, more preferably 400r / min-500r / min; the ball milling time is 2h-8h, more preferably 3.5h-5h; Or, the solvothermal method described in step 1) comprises the following steps: a. Transferring the sodium source, iron source, manganese source, vanadium source, A source, phosphorus source, carbon source and reducing agent into a polytetrafluoroethylene liner in a reaction kettle, and adding a solvent during mixing to obtain a precursor reaction liquid, wherein the solvent is water, ethanol, or a mixed solvent of water and ethanol, wherein the mass of water in the mixed solvent preferably accounts for (30-80) wt%, more preferably (45-55) wt%, and the mass of ethanol preferably accounts for (20-70) wt%, more preferably (45-55) wt%; b. Transfer the precursor reaction liquid to a forced air drying oven at a temperature of 120°C-200°C, more preferably 150°C-180°C; set the time to 8h-20h, more preferably 8h-12h; after the above process is completed, take out the reactor, pour out the upper reaction liquid, transfer the solid precipitate at the bottom of the reactor to a centrifuge tube, wash it with deionized water and ethanol three to five times respectively, collect the precipitated material after washing, transfer it to a forced air drying oven at a temperature of 80°C-120°C, more preferably 95°C-105°C, and obtain the solid precursor after drying.
5. The preparation method according to claim 3 or 4, characterized in that: Preferably, the phosphate pyrophosphate composite polyanionic compound has a structure as shown in Formula I, and the molar ratio of the sodium source, the iron source, the manganese source, the vanadium source, the A source, and the phosphorus source is 4:(3-x-1.5yz):x:y:z:4, and the molar ratio of the sodium source, the iron source, the manganese source, the vanadium source, the A source, and the phosphorus source is based on the molar amount of the sodium element, the iron element, the manganese element, the vanadium element, the A element, and the phosphorus element, respectively; Preferably, the amount of the reducing agent added should ensure that the molar ratio of the reducing agent, iron source, manganese source, vanadium source, and A source is (3-4):(3-x-1.5yz):x:y:z, and more preferably (3-3.5):(3-x-1.5yz):x:y:z; and it should ensure that the iron and manganese in the phosphate pyrophosphate composite polyanionic compound are both Fe 2+ , Mn 2+ 、V 3+ .
6. The preparation method according to claim 3 or 4, characterized in that: The sodium source is selected from at least one or more of sodium hydroxide, sodium ethoxide, sodium ascorbate, sodium carbonate, trisodium phosphate, sodium phenol, sodium carboxymethyl starch, sodium formate, sodium nitrite, sodium bicarbonate, sodium acetate, sodium citrate, sodium oxalate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium pyrophosphate, and sodium hydrogen pyrophosphate; The iron source is selected from one or more of iron powder, ferroferric oxide, ferrocene, iron carbide, ferrous oxide, ferric oxalate, ferrous oxalate (dihydrate), ferrous lactate, ferric phosphate, ferric phosphide, ferric pyrophosphate, ferrous citrate, ferric nitrate, ferrous nitrate, ferric hydroxide, EDTA iron-sodium salt, ferric sulfate, ferrous sulfate, ferric chloride, ferrous chloride, sodium ferrocyanide, ferric acetate, ferrous ammonium sulfate, ferric citrate, ammonium ferric citrate, and sodium ferric citrate succinate; The manganese source is selected from one or more of manganese powder, manganese monoxide, manganese dioxide, manganese trioxide, manganese tetraoxide, manganese hydroxide, manganese carbonate, manganese sulfate, manganese chloride, manganese nitrate, manganese phosphate, manganous phosphate, manganese phosphide, manganese dihydrogen phosphate, manganese nitrate tetrahydrate, manganese oxalate, and manganese acetate; The vanadium source is selected from one or more of vanadium powder, vanadium carbide, sodium metavanadate, ammonium metavanadate, sodium orthovanadate, vanadyl oxalate, vanadium oxide, vanadium nitride, vanadium pentoxide, vanadium tetroxide, vanadyl sulfate, vanadyl acetylacetonate, and vanadium acetylacetonate; The A source is selected from one or more of oxides, hydroxides, carbonates, sulfates, chlorides, sulfates, phosphates, acetylacetonates, etc. corresponding to the metal ions; The phosphorus source is selected from at least one or more of diammonium phosphate, diammonium hydrogen phosphate, phosphoric acid, metaphosphoric acid, hypophosphorous acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, sodium hexametaphosphate, pyrophosphoric acid, sodium pyrophosphate, sodium hydrogen pyrophosphate, iron phosphate, iron phosphide, and manganese phosphate; The carbon source is selected from at least one or more of ethylene glycol, starch, carboxymethyl starch, sodium carboxymethyl starch, sodium alginate, citric acid, oxalic acid, ammonium citrate, ascorbic acid, formaldehyde, acetaldehyde, lactic acid, malic acid, glucose, sucrose, maltose, maltodextrin, dopamine, carbon nanotubes, redox graphene, phenolic resin, polyvinyl pyrrolidone, tannic acid, polyethylene glycol, and aniline; The reducing agent is selected from at least one or more of ethylene glycol, starch, carboxymethyl starch, sodium carboxymethyl starch, sodium alginate, citric acid, oxalic acid, ammonium citrate, ascorbic acid, formaldehyde, acetaldehyde, lactic acid, malic acid, glucose, sucrose, maltose, maltodextrin, dopamine, carbon nanotubes, phenolic resin, polyvinyl pyrrolidone, tannic acid, polyethylene glycol, and aniline; The addition of the carbon source and the reducing agent should ensure that the mass content of carbon in the phosphate-pyrophosphate composite polyanionic compound is 1wt%-12wt%, and more preferably 3wt%-8wt%.
7. The phosphate pyrophosphate composite polyanionic compound according to claim 3 or 4, characterized in that: The ball milling needs to add ball milling media, the speed of the ball milling in step 1) of claim 3 is 200-400 rpm / min, and the ball milling time is 2-4h; The ball milling medium is one or more of zirconium oxide beads, agate beads, and zirconium silicate beads, and the ball-to-material ratio (mass ratio of balls to solid materials) is 1.5-7; the diameter of the ball milling medium is 2-10 mm, preferably a combination of diameters of 3 mm, 5 mm, 7 mm, and 10 mm in a mass ratio of 1:2:1:1; The sanding process requires the addition of a sanding medium, the rotation speed of the sanding process is 1500-3000 rpm / min, and the sanding time is 1-8 hours; The sand grinding medium is one or more of natural sand beads, zirconia beads, and agate beads, and the ball-to-material ratio (mass ratio of balls to solid materials) is 1-5; the diameter of the sand grinding medium is 0.1-1mm, preferably a combination of diameters of 0.3mm, 0.5mm, 0.7mm, and 1mm in a mass ratio of 2:2:1:
1.
8. Use of the phosphate pyrophosphate composite polyanionic compound according to any one of claims 1 to 2 in a sodium ion battery, characterized in that: Phosphate-pyrophosphate complex polyanionic compounds are used as active substances of electrode materials for sodium ion batteries.
9. The use according to claim 8, characterized in that: Phosphate-pyrophosphate composite polyanion compound as positive electrode active material for sodium ion battery.
10. The use according to claim 9, characterized in that: In the positive electrode material, the content of the phosphate pyrophosphate composite polyanion compound electrode material is (60-98) wt%; The positive electrode material also contains a conductive agent and a binder, and the mass ratio of the phosphate pyrophosphate composite polyanionic compound, the conductive agent, and the binder is (60-98) wt%: (1-39) wt%: (1-39) wt%; The conductive agent is at least one or more of carbon black, conductive graphite, carbon fiber, carbon nanotube, and graphene; The binder is polyvinylidene fluoride: at least one or more of PVDF5130, HSV900 and kynar761A.
Citation Information
Patent Citations
Stationary, fluid redox electrode
CN103155257A
Positive electrode material for sodium ion battery and preparation method of positive electrode material
CN115241422A
Anion-cation functionalized doping modified high-entropy polyanionic positive electrode material, preparation method and application thereof
CN115360340A
Preparation method of phosphate-based polyanionic compound and application of phosphate-based polyanionic compound in sodium-ion battery
CN116344752A
Carbon-coated nmtvp nanocomposite positive electrode material, method for manufacturing same, and positive electrode and sodium ion battery comprising same
WO2022177246A1
Cited By
Carbon-coated ion-doped ferric sodium pyrophosphate positive electrode material and preparation method thereof
CN120440863A
Lithium iron phosphate composite electrode material and preparation method thereof
CN120878807A
A lithium iron phosphate composite electrode material and its preparation method
CN120878807B